Multivariate analysis in large cardamom (Amomum subulatum Roxb.) - K J Madhusoodanan, J Thomas, U Gupta, K M Kuruvilla, Priya P Menon, (Journal of Spices and Aromatic Crops, 2006)
The variability in large cardamom (Amomum subulatum) germplasm was studied by applica-tion of multivariate methods such as principal component analysis, discriminant functionanalysis and Hotelling’s T2 statistic. Variables such as girth of the clump, number of bearingtillers, number of spikes clump-1, number of capsules spike-1, capsule length, capsule diam-eter and capsule weight recorded in 40 accessions belonging to two cultivars of large carda-mom namely, Ramsey and Sawney were used in the study. Principal component analysis re-sulted in the identification of three components, which could explain 73% of variability inlarge cardamom. Discriminant function analysis brought about a discriminant function todistinguish between the two cultivars of large cardamom. Among the variables, capsuleweight, girth of the clump, capsules spike-1 and number of bearing tillers contributed maxi-mum towards yield and hence such characters can be effectively exploited in crop improve-ment programmes.